Adsorption of N2 and CO2 on Activated Carbon, AlO(OH) Nanoparticles, and AlO(OH) Hollow Spheres. Issue 12 (10th November 2015) - Reiser, Sarah; Bolten, Dennis; Staudt, Reiner; Türk, Michael
Abstract: Adsorption behaviors of nitrogen and CO2 on Norit R1 Extra and AlO(OH) nanoparticles and hollow spheres were measured under different temperature and pressure conditions using a magnetic suspension balance. Independent from the substrate investigated, all isotherms increase at lower pressure, reach a maximum, and then decrease with increasing pressure. In addition, selected experimental data were correlated with different model approaches and compared with reliable literature data. In case of CO2 on AlO(OH), capillary condensation was observed at two defined temperatures. The results suggest that the conversion of the liquid into a supercritical adsorbate phase does not take place suddenly. Abstract : Boehmite (AlO(OH)) nanoparticles and hollow spheres are a promising high‐surface material for various separation technique applications. Adsorption data of nitrogen and CO2 on activated carbon, AlO(OH) nanoparticles and hollow spheres were determined at various temperatures and pressures using a magnetic suspension balance. Selected modeling results are presented and discussed.